2017
DOI: 10.1099/jgv.0.000948
|View full text |Cite
|
Sign up to set email alerts
|

Novel polyomaviruses in shrews (Soricidae) with close similarity to human polyomavirus 12

Abstract: Shrews (family Soricidae) have already been reported to host microorganisms pathogenic for humans. In an effort to search for additional infectious agents with zoonotic potential, we detected polyomaviruses (PyVs) in common shrew, crowned shrew, and pygmy shrew (Sorex araneus, S. coronatus and S. minutus). From these, 11 full circular genomes were determined. Phylogenetic analysis based on large T protein sequences showed that these novel PyVs form a separate clade within the genus Alphapolyomavirus. Within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
2
17
2
Order By: Relevance
“…In contrast to our data, a very recent study reported 90% seroprevalence for HPyV12, in an Italian adult population [36]. This percentage is considerably higher than our finding and the 20% seroprevalence obtained previously for HPyV12 by Ehlers and co-workers using recombinant VP1 and VP1-based VLP ELISA [34,37]. Since HPyV VP1-based and VLP based assays generally obtain comparable results, as we have recently demonstrated for BKPyV [19], we have no explanation thus far for this large discrepancy except differences in cut-off value determination and striking geographic differences in virus exposure.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our data, a very recent study reported 90% seroprevalence for HPyV12, in an Italian adult population [36]. This percentage is considerably higher than our finding and the 20% seroprevalence obtained previously for HPyV12 by Ehlers and co-workers using recombinant VP1 and VP1-based VLP ELISA [34,37]. Since HPyV VP1-based and VLP based assays generally obtain comparable results, as we have recently demonstrated for BKPyV [19], we have no explanation thus far for this large discrepancy except differences in cut-off value determination and striking geographic differences in virus exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we believe the observed low seroprevalence of these polyomaviruses to be genuine, and we consider the possibility that these polyomaviruses do not frequently circulate in humans, and perhaps do not represent human polyomaviruses at all. For HPyV12, this would fit with recent observations suggesting that HPyV12 represents a shrew rather than a human polyomavirus [34]. For NJPyV it could very well be that the only published patient was infected from an animal reservoir under exceptional circumstances, when fleeing from flooding during hurricane Sandy [35].…”
Section: Discussionsupporting
confidence: 65%
“…For HPyV12, in all 10 PCR‐positive samples human genomic DNA was detected, which is probably amplified in a non‐specific manner, because of the absence of specific DNA template. Furthermore, the finding of a PyV similar to HPyV12 in shrews combined with a reported low seroprevalence suggests little circulation of this virus in humans.…”
Section: Discussionmentioning
confidence: 96%
“…In members of some mammalian orders (e.g. primates, artiodactyls or rodents) many PyVs and HVs have been identified, some of which are well studied [29][30][31][32][33]. Despite this knowledge, information on PyVs and HVs is still scarce for many mammalian families.…”
Section: Introductionmentioning
confidence: 99%